Trade multilateralism : alive and well despite Trump - Rana, Pradumna B. (2020)
Many analysts have argued that with the election of President Trump, the rules-based multilateral trading system established in the post-World War II period has ended. This view is wrong. Trade multilateralism has taken a different form and is functioning fairly well.